Code Tracking Performance Analysis of GNSS Receivers with Blanking Model under Periodic Pulse Interference - P. Ma; X. Tang; S. Lou; K. Liu; G. Ou (Radioengineering, 2021)
As one of the most common types of interference, pulse interference and its suppression methods have been widely studied, in which the blanking method consumes less hardware resources and it is more commonly used in the Global Navigation Satellite System (GNSS) receivers. Previous studies used carrier-to-noise ratio (CNR) as an indicator to evaluate the performance of the receiver after pulse suppression. However, CNR is not the most important parameter that should be measured. The main function of the GNSS receiver is to measure the distance between the satellite and the receiver. How the pulse interference with different periods and duty cycle affects the ranging performance of the navigation receiver after blanking has not been fully studied. This paper focuses on the influence of the blanking method on the code tracking performance. Through derivation and simulation, it can be found that the ranging accuracy of the delay locked loop may not be deteriorated sometimes when the blanking operation plays a role of narrow correlation and the frequency of the pulse interference is close to the pseudo code. However, the blanking algorithm will cause large code tracking deviation, which will seriously affect the ranging performance of the receiver.